2011
DOI: 10.1177/1475090211418747
|View full text |Cite
|
Sign up to set email alerts
|

Measures of vibration exposure for a high-speed craft crew

Abstract: The paper compares measurement-based measures for human vibration exposure. Data were collected during sea trials on a 10 m, 50 kn coastguard craft equipped with a three-axial accelerometer at the coxswain seat and with vertically mounted gauges measuring the acceleration of the cockpit floor. The ISO 2631-1:1997 measures of vibration (namely the root-mean-square (r.m.s.) value of the whole-body vibration (determined from the frequency-weighted acceleration signal), the maximum transient vibration value (MTVV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…1 The experiment data consist of 12 sets of vertical accelerations of the seat base, € z b, exp , and the human-seat interface, € z 1, exp . Using the seat base acceleration € z b, exp as model input, the seat acceleration € z 1 is determined and then compared to the corresponding measured signal € z 1, exp .…”
Section: Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The experiment data consist of 12 sets of vertical accelerations of the seat base, € z b, exp , and the human-seat interface, € z 1, exp . Using the seat base acceleration € z b, exp as model input, the seat acceleration € z 1 is determined and then compared to the corresponding measured signal € z 1, exp .…”
Section: Validationmentioning
confidence: 99%
“…Back pains, headache and tiredness in connection to duty are common health problems among HSC operators. 1 Other reported problems are acute injuries to the back, knees, neck and shoulders. 2 The motions of HSC can also reduce the crew’s physical ability and cause muscle damage and fatigue, 3 which adversely affect the crew’s decision-making capacity and ability to perform their task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 According to a survey conducted by the US Naval Health Research Centre, 95% of the reported injuries that required hospitalization were attributed to the motions of the craft. 7 Furthermore, Garme et al 6 and Allen et al 8 show that daily exposure limits, set by the European Union directive 9 of whole body vibrations (WBVs), may be exceeded in a matter of minutes on a high-speed craft in rough conditions. This article investigates the consequences of the selection of material concept on the rough water performance and the effect of different ballast configurations for a high-speed patrol vessel.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by KTH Royal Institute of Technology and Umeå University in collaboration with the Swedish Coast Guard show that the statutory vibration exposure action and limit values 11–13 are exceeded after a short time of exposure. 14 This indicates that severe conditions are common and the fact that the exemption of statutory laws for seaborne and airborne occupations seems contradictory. 11 Consequentially, the measures to assess the working conditions aboard marine vehicles related to risk for health impairments and performance deteriorations are in debate, 14–20 together with the question on how to interpret the measures.…”
Section: Introductionmentioning
confidence: 99%